On the application of Ateb-functions to the construction of an asymptotic solution of the perturbed nonlinear Klein-Gordon equation - Mitropolskiy, Yu. A.; Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For the perturbed nonlinear Klein-Gordon equation, we construct an asymptotic solution by using Ateb-functions. We consider autonomous and nonautonomous cases.